2012
DOI: 10.1007/s00280-012-1821-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and pharmacokinetics of amuvatinib from three phase 1 clinical studies in healthy volunteers

Abstract: Amuvatinib LSC, 300 mg every 8 h, is being studied in cancer patients based on the improved exposure and similar safety profile to amuvatinib DPC. A lipid-based formulation approach may be a useful tool for other low aqueous soluble compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The plasma levels of the drug were generally low and highly variable. This limitation led to the development of a new lipid-suspension capsule formula that was tested in healthy volunteers in another phase I clinical trial [64] and showed better bioavailability compared to the dry powder capsule formula. Both formulas were well tolerated and showed a good safety profile.…”
Section: Kit and Pdgfra Inhibitorsmentioning
confidence: 99%
“…The plasma levels of the drug were generally low and highly variable. This limitation led to the development of a new lipid-suspension capsule formula that was tested in healthy volunteers in another phase I clinical trial [64] and showed better bioavailability compared to the dry powder capsule formula. Both formulas were well tolerated and showed a good safety profile.…”
Section: Kit and Pdgfra Inhibitorsmentioning
confidence: 99%
“…Phase 1 clinical studies have shown single-agent amuvatinib to be safe and well tolerated [ 12 , 13 ], with amuvatinib exposures significantly improved when lipid-suspension capsules rather than dry-powder capsules are administered [ 12 ]. In addition, Mita et al [ 14 ] showed preliminary evidence of anti-tumor activity and durable SD (up to 708 days) with amuvatinib administered at varying dose levels in combination with standard chemotherapy agents.…”
Section: Introductionmentioning
confidence: 99%
“…79 Inhibition of AXL using 13 reversed EMT in murine breast cancer stem cells, reducing self-renewal and restoring sensitivity to chemotherapy. 80 After phase I evaluation in patients with solid tumors, 81 13 entered a phase II clinical trial in patients with NSCLC in combination with standard of care chemotherapy (platinum and etoposide, structures not disclosed). Despite favorable safety and preliminary clinical activity in the first stage of this phase II, Astex Pharmaceuticals announced discontinuation of its clinical development in 2012.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%